2013
DOI: 10.1104/pp.113.217844
|View full text |Cite
|
Sign up to set email alerts
|

Growth Platform-Dependent and -Independent Phenotypic and Metabolic Responses of Arabidopsis and Its Halophytic Relative, Eutrema salsugineum, to Salt Stress

Abstract: Comparative studies of the stress-tolerant Arabidopsis (Arabidopsis thaliana) halophytic relative, Eutrema salsugineum, have proven a fruitful approach to understanding natural stress tolerance. Here, we performed comparative phenotyping of Arabidopsis and E. salsugineum vegetative development under control and salt-stress conditions, and then compared the metabolic responses of the two species on different growth platforms in a defined leaf developmental stage. Our results reveal both growth platform-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 92 publications
5
47
0
Order By: Relevance
“…In addition to being salt-tolerant (e.g., Inan et al, 2004; Taji et al, 2004; Kant et al, 2006), E. salsugineum is also tolerant to low soil nitrogen (Kant et al, 2008), high boron levels (Lamdan et al, 2012), low phosphate levels (Velasco et al, 2016), heat stress (Higashi et al, 2013), and shows similar tolerance to cold and freezing stress as Arabidopsis (Griffith et al, 2007; Lee et al, 2012). A number of factors contribute to E. salsugineum stress tolerance including constitutive up- and down-regulation of stress tolerance genes and metabolites suggesting that E. salsugineum is “primed” for stress, gene copy number expansion of ion transport-related genes, sub-functionalization and neo-functionalization of duplicated genes, biased codon usage facilitating more efficient translation of proteins related to ion transportation, and the possible involvement of lineage-specific genes (Taji et al, 2004; Gong et al, 2005; Kant et al, 2006, 2008; Lugan et al, 2010; Oh et al, 2010, 2012, 2014; Sun et al, 2010; Dassanayake et al, 2011; Wu et al, 2012; Champigny et al, 2013; Kazachkova et al, 2013; Yang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to being salt-tolerant (e.g., Inan et al, 2004; Taji et al, 2004; Kant et al, 2006), E. salsugineum is also tolerant to low soil nitrogen (Kant et al, 2008), high boron levels (Lamdan et al, 2012), low phosphate levels (Velasco et al, 2016), heat stress (Higashi et al, 2013), and shows similar tolerance to cold and freezing stress as Arabidopsis (Griffith et al, 2007; Lee et al, 2012). A number of factors contribute to E. salsugineum stress tolerance including constitutive up- and down-regulation of stress tolerance genes and metabolites suggesting that E. salsugineum is “primed” for stress, gene copy number expansion of ion transport-related genes, sub-functionalization and neo-functionalization of duplicated genes, biased codon usage facilitating more efficient translation of proteins related to ion transportation, and the possible involvement of lineage-specific genes (Taji et al, 2004; Gong et al, 2005; Kant et al, 2006, 2008; Lugan et al, 2010; Oh et al, 2010, 2012, 2014; Sun et al, 2010; Dassanayake et al, 2011; Wu et al, 2012; Champigny et al, 2013; Kazachkova et al, 2013; Yang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…To obtain a global view of the differences between the plant species and across the treatments, Kazachkova et al (2013), applied the principal component analysis (PCA), and the inspection of the first two components accounted for 78.5% of the total variance that allowed classification of samples by species. Our PCA showed that species was the predominant factor explaining differences between them with 65.63% of the total variance explained (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because all these species were under the same wild culture condition and evaluated at the same time and similar age. Like in Arabidopsis taliana, Kazachkova et al (2013) studied different treatment and growth platform and determined that the samples were clearly clustered according to the species first, and also clear subclades were observed separated by growth platform. Also, similar results were reported in Eutrema salsugineum by Guevara et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we demonstrated that constitutive down-regulated expression of E. salsugineum PDH, encoding the proline catabolic enzyme, proline dehydrogenase, is correlated with increased levels of the osmoprotectant, proline, under control and salt-stress conditions in E. salsugineum shoots compared to Arabidopsis [21]. At the level of global primary metabolism, specific features of the E. salsugineum salt metabolome can be observed such as constitutively higher levels of TCA cycle intermediates, malate and citrate but constitutively lower levels of fumerate and the osmoprotectants, raffinose and galactinol, compared to Arabidopsis [25]. Interestingly, many metabolites are repressed in E. salsugineum when plants are grown in vitro on nutrient agar plates compared to soil-grown plants, yet the plants retain their salt tolerance under both growth conditions.…”
mentioning
confidence: 98%